On the Role of Sensory Feedbacks in Rowat–Selverston CPG to Improve Robot Legged Locomotion - Amrollah, Elmira; Henaff, Patrick (Frontiers in Neurorobotics, 2010)
This paper presents the use of Rowat and Selverston-type of CPG to control locomotion. It focuses on the role of afferent exteroceptive and proprioceptive signals in the dynamic phase synchronization in CPG legged robots. The sensori-motor neural network architecture is evaluated to control a two-joint planar robot leg that slips on a rail. Then, the closed loop between the CPG and the mechanical system allows to study the modulation of rhythmic patterns and the effect of the sensing loop via sensory neurons during the locomotion task. Firstly simulations show that the proposed architecture easily allows to modulate rhythmic patterns of the leg, and therefore the velocity of the robot. Secondly, simulations show that sensori-feedbacks from foot/ground contact of the leg make the hip velocity smoother and larger. The results show that the Rowat-Selverston-type CPG with sensory feedbacks is an effective choice for building adaptive Neural Central Pattern Generators for legged robots.